PENGGUNAAN SINGKATAN DAN AKRONIM DALAM BERITA KRIMINAL HARIAN TRIBUN JAMBI PADA BULAN MARET 2019 - Avra Jumasha Refri Asih; Uli Wahyuni (Universitas Batanghari, 2019)
The purpose of this research is to describe the abbreviation form and acronym used in the criminal daily news of Tribun Jambi March edition 2019. This type of research is a qualitative descriptive. The data are taken from the daily issue of Tribun Jambi March edition 2019. The technique of collecting the data is documentation. The results show that, from all 16 data, there are only 4 forms of acronyms and 1 abbreviation form were found in the daily criminal news of Tribun Jambi March edition 2019. From all three forms of the acronym, there is 2 quotations which represents the first letter of the acronym; there is 7 quotations which represents the first two-letter retention of each component; theere is 10 quotations which represents the first three-letter for each component; and there are 12 quotations which represents the retention of many letters and syllables that are difficult to formulate. While on the abbreviation, it is found only the first letter retention of each component as much as 51 quotations.